Analisis Fiqh Muamalah Terhadap Praktik Giveaway Bersyarat di Akun Instagram @Giveaway.Oyi - Aimana, Muftia Tsabita; Fahrullah (Jurnal Ekonomika dan Bisnis Islam, 2022)
The practice of giveaways has begun to be widely used by various groups, from online shops on the Instagram, personal accounts to become celebrities, official or community accounts and others. The goals also vary, some are for promoting new products, increasing followers, and increasing Instagram insights. This study aims to determine the contract used in the practice of conditional giveaways on the @Giveaway.Oyi Instagram account, implementing a giveaway system that involves sponsors and the prize being distributed is cash by asking for opinions from one of the figures who understand the science of fiqh muamalah. The data in this study were collected by the field research method by conducting interviews and observations to related parties supported by documentation data. This study succeeded in concluding that the conditional giveaway practice applied to the @Giveaway.Oyi Instagram account includes service rental (ujrah) and there is no element of gambling (maisir) during the implementation of the giveaway practice on the @Giveaway.Oyi Instagram account.